Radar system analysis, design, and simulation - Kang, Eyung W. (Artech House, 2008)
This book helps you master critical system analysis and design skills, and shows you how to use digital computer simulation to verify that an analysis is correct and that a design is optimal. This comprehensive resource covers a wide range of essential topics, from matrix, vector and linear equations, noise and clutter generation, Filters (FIR and IIR), and fast Fourier transforms ... to ambiguity functions, antennas, target detection, and the Kalman filter ... to the Monte Carlo method, constant false alarm rate (CFAR) processing, and moving target indicators (MTI).